THE IMPACT OF DRUG USE ON THE FAMILY RELATIONSHIPS OF DRUG ADDICTS - Miriam Aparecida Nimtz; Anna Maria Fornalski Tavares; Mariluci Alves Maftum; Aline Cristina Zerwes Ferreira; Letícia de Oliveira Borba; Fernanda Carolina Capistrano (Universidade Federal do Paraná, 2014)
This work aims to identify the impact of drug use on the family relationships of drug addicts. It is exploratory qualitative research, undertaken in a rehabilitation unit for drug addicts in the Brazilian state of Paraná. Ethical principles - in accordance with Resolution 196/96 - were respected. The data were collected through semistructured interviews, held in the period August - September 2012 with 20 drug addicts. The data were treated using thematic categorical analysis. The categories analyzed were: Influence of family relationships on drug use and Breaking family bonds. It is concluded that drug addiction is an illness which affects the relationships, impairing the quality of life of the addicts and their family members. Thus, the importance of trained health professionals is emphasized, with a view to attention for this clientele.